A critical look at meta‐analytic evidence for the cognitive approach to lie detection: A re‐examination of Vrij, Fisher, and Blank (2017). (11th September 2017) - Levine, Timothy R.; Blair, J. Pete; Carpenter, Christopher J.
Abstract : Purpose: This article provides a re‐analysis of Vrij et al .'s (2017, Leg. Crim. Psychol . 22, 1) meta‐analysis of the cognitive approach to lie detection. Vrij et al .'s analyses confounded dependent variables, capitalized on aberrant controls, and used unreliable data to inflate support. Methods: Meta‐analysis was used to reanalyse Vrij et al .'s data. Studies of human detection and studies involving statistical classification were analysed separately. Results: The advantage offered by the cognitive approach was much smaller than previously claimed. Accuracies in control conditions were unusually low, and the most supportive findings came from the least reliable data. Conclusions: Human detection and statistical classification are different. The evidence for the cognitive approach has been overstated.